Probiotic and postbiotic analytical methods: a perspective of available enumeration techniques - Boyte, Marie-Eve; Benkowski, Andrzej; Pane, Marco; Shehata, Hanan R. (Frontiers in Microbiology, 2023)
Probiotics are the largest non-herbal/traditional dietary supplements category worldwide.To be effective, a probiotic strain must be delivered viable, at an adequate dose proven to deliver a health benefit. The objective of this article is to give an overview of the various technologies for probiotic enumeration including a general description of each technology, their advantages and limitations, and their potential for the future of the probiotics industry.The "gold standard" for analytical quantification of probiotics in the probiotic industry is the Plate Count method (PC). PC measures the bacterial cell's ability to proliferate into detectable colonies, thus the method relies on cultivability as a measure of viability.Although viability has widely been measured by cultivability, there has been agreement that the definition of viability is not limited to cultivability. For example, bacterial cells may exist in a state known as viable but not culturable (VBNC) where the cells lose cultivability but can maintain some of the characteristics of viable cells as well as probiotic properties. This led to questioning the association between viability and cultivability and the accuracy of PC methods in enumerating all the viable cells in probiotic products. PC has always been an estimate of the number of viable cells and not a true cell count.Additionally, newer probiotic categories such as Next Generation Probiotics (NGPs) are not easy to culture in routine laboratories because NGPs are often strict anaerobes with extreme sensitivity to atmospheric oxygen. Thus, quantification using culture-based techniques will be complicated. Another emerging category of biotics is postbiotics, which are inanimate microorganisms, also often referred to as tyndallized or heat-killed bacteria.Obviously, culture dependent methods are not suitable for these products, and alternative methods are needed for their quantification. Different methodologies provide a more complete picture of a heterogeneous bacterial population versus PC method focusing exclusively on the eventual multiplication of the cells. Alternative culture-independent techniques including real-time PCR, digital PCR and flow cytometry are discussed. These methods can measure viability beyond cultivability (i.e., by measuring cellular enzymatic activity, membrane integrity or membrane potential), and depending on how they are designed they can achieve strain-specific enumeration.